SURGICAL INTERVENTIONS TO TREAT INFERTILITY IN RUMINANTS SPECIFICALLY DAIRY ANIMALS - KHAN, S; MANZOOR, H; MATEEN, A; USMAN, M; SHAH, S; HASAN, W; SAMAD, A; ALI, A; MUZAMMIL, M; REHMAN, M; FATIMA, M; AHMAD, S (Biological and Clinical Sciences Research Journal, 2024)
The role of the dairy industry is significant in the agricultural sector since it supplies much-required goods to the global food industry. Objectives: The main objective of the study is to find surgical interventions to treat infertility in ruminant’s specifically dairy animals. Methodology of the study: This retrospective study design was conducted at farms in the vicinity of district Lahore from March 2023 to March 2024. 240 dairy cows and heifers were selected based on criterion. These were animals presented for diagnosis by a veterinarian with clinical signs, reproductive examination, and laboratory examination suggesting that they were infertile. Samples were selected from different places ensuring that it cuts across different types of dairy farms in terms of management practices and the type of environment the farms are located in within the study area. Results: Data were collected from 240 dairy cows. Among the 240 participants, with an average age of 4.2 years, Holstein Friesian constituted the majority breed, accounting for 62.5%, followed by Jersey (20.8%) and other breeds (16.7%). Parity distribution revealed that 33.3% were primiparous (first calving) while 66.7% were multiparous. Procedures that were focused on this general area of operative criteria showed desirable results. Compared to women with adnexal adhesions, women with uterine adhesions exhibited similar recovery profiles; in 100 cases of adhesiolysis, 80% of patients displayed better reproductive outcomes post-surgery. Conclusion: It is concluded that surgical interventions play a crucial role in enhancing fertility outcomes among dairy ruminants, offering effective solutions for addressing reproductive abnormalities.